Budgets for Acquisitions: Strategies for Serials, Monographs and Electronic Formats, 1st edition - Lee, Sul H. (Routledge, 2020)
This book, first published in 1991, deals with the demanding problems of smaller acquisitions budgets. In recent years librarians have seen their finances diminishing while the prices of serials and monographs have risen steadily. Now with major decisions having to be made concerning such things as automation, monograph collections, and subscription renewals, librarians are having to assume the role of business manager and dealer. This book takes an in-depth look at the situation and offers practical suggestions for working through the lean years. Strategies for getting the most for your money when dealing with vendors, selective collection development and maintenance, and making calculated decisions on how to divide the library's funds are just a few of the topics covered in this helpful new book.